Strategi Bahasa Persuasif dalam Takarir Lip Cream Instagram @itsomgbeauty: Analisis Linguistik Sistemik Fungsional - Nadya Ihsanita; Muhammad Badrus Siroj (Paedagogie, 2026)
This study aims to describe the use of sentence types as persuasive language strategies in the captions of lip cream posts on the Instagram account @itsomgbeauty and to analyze the ideational, interpersonal, and textual metafunctions based on Systemic Functional Linguistics (SFL) theory. This study employs a qualitative descriptive approach, with data sources consisting of eight captions for lip cream posts uploaded to the Instagram account @itsomgbeauty in 2025. Data were selected through purposive sampling and collected using documentation techniques. Data analysis was conducted through the stages of identification, classification, analysis, and drawing conclusions. The results of the study show that persuasive language strategies in subtitles are constructed through the use of declarative, imperative, interrogative, and exclamatory sentences. Declarative sentences are the most dominant type used because they serve to convey information about the product’s advantages. Imperative sentences are used to encourage the audience to take specific actions, interrogative sentences are used to increase audience engagement, while exclamatory sentences are used to reinforce the emotional aspect of the promotional message. Additionally, the ideational, interpersonal, and textual metafunctions are used in an integrated manner to construct persuasive messages. The ideational metafunction represents the product and user experience; the interpersonal metafunction builds a relationship between the brand and the audience; and the textual metafunction organizes the message for easy understanding. Thus, the persuasion strategy in digital cosmetic promotions is built through a combination of informative, interactive, and persuasive language functions.